Identifikasi Penggunaan Alat Pelindung Diri (APD) dan Kecelakaan Akibat Kerja Pada Pemulung di TPA Tamangapa Raya - Sahani, Wahyuni; Sartika, Sartika (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
The problem of waste at the Tamangapa Raya Landfill is still a problem in Makassar city. Waste disposal access at the landfill has exceeded capacity because the production of waste generated by the community continues to grow and results in limited access for transport vehicles and becomes an obstacle when entering the landfill so that there is a buildup of garbage trucks along the entrance to the landfill. Scavengers are one of the workers at the landfill who help reduce waste by taking unused items made of plastic, cardboard, and iron that can be sold and recycled again. The purpose of this study to identify the use of Personal Protective Equipment (PPE) and Occupational Accidents to scavengers at Tamangapa Raya Landfill. This type of research conducted was descriptive. The sample in this study amounted to 91 waste pickers. Data obtained by observation and interview methods by filling out questionnaires. The results showed that there were 76 waste pickers (83.51%) used helmet/hat, 37 people (40.65%) used mask, 69 people (75.82%) used work clothes, 53 people (58.24%) used gloves and 81 people (89.01%) used boots. Meanwhile, 63 waste pickers (69.23%) fell, 32 people (35.16%) bumped, 36 people (39.56%) slipped, 75 people (82.41%) were punctured, 49 people (53.84%) were sprained, 24 people (26.37%) were crushed, 73 people (80.21%) were pinched, 17 people (18.68%) and 67 people (73.62%) were tripped. The advice for scavengers at Tamangapa Raya Landfill should pay more attention to the completeness of Personal Protective Equipment (PPE) such as helmets/hats, masks, gloves, work clothes and boots to minimize risks and prevent occupational accidents. Keywords : Scavengers; Personal Protective Equipment (PPE); Occupational Accidents Work; Landfill